Optimal control for large-scale interconnected discrete-time systems with uncertain parameter using singular perturbation methods - Zhou, J.; Challoo, R. (29th IEEE Conference on Decision and Control, 1990)
A two-time-scale large-scale discrete-time system with an uncertain parameter is considered. It is assumed that a specific structure of m-1 lower level 'fast' subsystems is interconnected through the dynamics of a higher level 'slow' subsystem. Near-optimal solutions are obtained, such that not only is the given cost functional minimized, but also the sensitivity of the interconnected system with respect to the uncertain parameter is reduced.< >